Gut microbiota community and metabolic profiles in direct total cavopulmonary connection and Fontan circulation: a cross-sectional study in the single center - Wang, Kaiyu; Han, Linjiang; Ma, Jianrui; Fang, Yushen; He, Yinru; Liu, Xiaobing; Wen, Shusheng; Zhuang, Jian; Yuan, Haiyun (Frontiers in Microbiology, 2025)
BackgroundThis study aimed to evaluate the impact of the direct total cavopulmonary connection (dTCPC) procedure on the gut microbiome and metabolome. It also sought to elucidate the features of the gut microbiota community and metabolic profiles in Fontan circulation.MethodsWe randomly recruited 45 participants above 14 years old undergoing Fontan procedure by typical extracardiac conduit (TCPC group, n = 15), direct total cavopulmonary connection (dTCPC group, n = 16) procedure and healthy control (control group, n = 14) in our institution between May 2023 and October 2023. 16S rRNA amplicon sequencing and untargeted metabolites measurement were performed on their fecal sample.ResultsThe four alpha diversity indexes showed no statistical significance between the dTCPC and TCPC groups (p > 0.05). Orthogonal partial least squares discriminant analysis (OPLS-DA) followed by permutation testing indicated an overfitting effect in the model between the dTCPC and TCPC groups. We observed significant differences in the Chao1 index (p = 0.0236), the ACE index (p = 0.0236), and the unweighted beta diversity (p = 0.0099) between the Fontan group and healthy control group. Strains of Fusobacterium were significantly overrepresented in the Fontan group [with linear discriminant analysis (LDA) scores exceeding (log10) >3]. Functional enrichment analysis revealed a significant overrepresentation of several metabolic pathways. These pathways predominantly included those related to amino acid metabolism, such as histidine metabolism, glycine, serine, and threonine metabolism, and cysteine and methionine metabolism. Additionally, the biosynthesis of unsaturated fatty acids was also notably enriched.ConclusionThe dTCPC procedure demonstrated similar gut microbiota composition and metabolic profiles to the traditional ECC procedure in Fontan patients. Notably, the increased abundance of Fusobacterium, reduced microbial biodiversity, and altered metabolic profiles of amino acids and unsaturated fatty acids in the alimentary canal may serve as distinctive characteristics of patients who have undergone Fontan circulation. These findings provide valuable insights into the long-term physiological consequences of Fontan procedure and may inform future clinical management strategies.